2014
DOI: 10.1111/jre.12229
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the developmental origins of the periosteum may influence bone healing

Abstract: Jaw bone periosteum exhibits a unique gene expression profile that is associated with neural crest cells and has a positive influence on bone regeneration when used as a graft material to repair bone defects. A full investigation of the biological and mechanical properties of jaw bone as an alternative graft material for jaw reconstructive surgery is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Despite the histological similar appearance of the mesoderm- and CNCC-derived bones, the CNCC-derived bones of the jaw for example differ biologically; they possess distinct gene expression signatures, higher alkaline phosphatase activity, higher proliferation and greater regenerative capabilities (Heuze et al, 2014; Hochgreb-Hagele et al, 2015; Ichikawa et al, 2015; Quarto et al, 2010). Identifying the role of local signaling pathways that help to properly develop these cartilage structures is critical to the understanding of the precise shape and size that bones acquire, a requisite for their function.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the histological similar appearance of the mesoderm- and CNCC-derived bones, the CNCC-derived bones of the jaw for example differ biologically; they possess distinct gene expression signatures, higher alkaline phosphatase activity, higher proliferation and greater regenerative capabilities (Heuze et al, 2014; Hochgreb-Hagele et al, 2015; Ichikawa et al, 2015; Quarto et al, 2010). Identifying the role of local signaling pathways that help to properly develop these cartilage structures is critical to the understanding of the precise shape and size that bones acquire, a requisite for their function.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, Ichikawa et al 27 previously reported abundant bone marrow-like tissue in the regenerated tissue of animals receiving transplanted maxillary bone and periosteum. Osteopontin promotes early differentiation of osteoblasts, their adhesion to bone, and subsequent bone formation.…”
Section: Discussionmentioning
confidence: 96%
“…For example, mandibular bone exhibits a higher proliferation, alkaline phosphatase activity, and has a distinct gene expression profile than the mesodermal bone in the tibia (Reichert et al, 2013). These differences are also observed between neural crest-derived tissue in the flat bones of the skull and long mesodermal bones, with increased periosteal response in crest versus mesoderm-derived bone healing (Ichikawa et al, 2014) and distinct susceptibility to mutations in FGFR2 S252 displayed in cranial bone such as the severe phenotypes observed in the Apert syndrome (Heuze et al, 2014).…”
Section: Introductionmentioning
confidence: 86%